The Analysis of Students’ Spatial Ability at Senior High School in Banda Aceh - Nanda Rahmatulwahidah; Cut Morina Zubainur (Proceedings of AICS - Social Sciences, 2017)
Spatial ability is one of the abilities required during mathematics teaching learning process in schools based on the curriculum’s mandate. To deal with, teachers should be able to choose a learning approach that is able to develop the capability. Spatial ability can be measured through the ability to rotate, alter, move, perceive an object and also determine the relationship between one part with other parts. Furthermore, this skill can be noticed of the ability to identify the basic logic of a pattern and determine the solution which is called as the abstract reasoning.This study aims to describe the spatial ability of the second grade of high school. The research involved 30 students of grade XI IPA 3 at such as one of senior high school in Banda Aceh. The instruments used in this research were spatial ability test and semi structured interview. The results of this study show that most of the students were able to determine the rotation of an object and abstract reasoning on the archetype. However, there is a minor percentage of students who were able to visualize, perceive, and determine the relationship between a part and other parts of a three-dimensional object. Keywords:Analysis, spatial ability, mathematic, geometry.